The Effect of Service Officer Performance on Passenger Satisfaction at the South Sulawesi Railway Management Center - Miftahul Huda Asmin (Atha Publishing Globalindo, 2026)
This study aims to find out how the performance of service officers affects passenger satisfaction at the South Sulawesi Railway Management Center. In this research, a quantitative method with an associative approach is used. The data collection technique was through a questionnaire distributed to 100 respondents. Data analysis using simple linear regression with the help of spss 10.0 software. This study shows that all question items are declared valid and reliable with a Cronbach's Alpha value of 0.896. The results of the regression analysis showed that Officer Performance had a positive and significant influence on Passenger Satisfaction with a significance value of 0.000 < 0.05. The value of the determination coefficient (R2) obtained was 0.662 indicating that the effect of officer performance on passenger satisfaction was 66.2%, while the rest was influenced by other variables outside this study. Thus, the better the performance of the officers, the higher the level of passenger satisfaction.